Deep Convolutional Feature Extraction and Brain Morphometry Intelligence: AI-Powered Computational Solutions for Enhanced Neuroimaging Analysis and Interpretation (Journal of Science & Technology, 2025)
Neuroimaging and machine learning are two cutting-edge, exciting fields that have the ability to reshape our world over the next decades. A conflux of these two fields is particularly appealing because of the immense need and potential of tech-enabled neuroimaging applications. Neuroimaging refers to a series of noninvasive neurophysiological techniques used in medicine to visualize the structure, function, and the tiniest level of detail of the brain.